2020
DOI: 10.1186/s40478-020-00990-x
|View full text |Cite
|
Sign up to set email alerts
|

Towards an improved early diagnosis of neurodegenerative diseases: the emerging role of in vitro conversion assays for protein amyloids

Abstract: Tissue accumulation of abnormal aggregates of amyloidogenic proteins such as prion protein, α-synuclein, and tau represents the hallmark of most common neurodegenerative disorders and precedes the onset of symptoms by years. As a consequence, the sensitive and specific detection of abnormal forms of these proteins in patients' accessible tissues or fluids as biomarkers may have a significant impact on the clinical diagnosis of these disorders. By exploiting seeded polymerization propagation mechanisms to obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 96 publications
(181 reference statements)
0
44
0
Order By: Relevance
“…Of course, RT-QuIC assays have revolutionized the diagnostic approach not only in human prion disorders but also in other proteinopathies and in particular in α-synucleinopathies. 32 , 33 Previous studies showed that α-syn RT-QuIC detects α-syn aggregates in CSF of patients with DLB, with high diagnostic accuracy. 12–17 …”
Section: Discussionmentioning
confidence: 99%
“…Of course, RT-QuIC assays have revolutionized the diagnostic approach not only in human prion disorders but also in other proteinopathies and in particular in α-synucleinopathies. 32 , 33 Previous studies showed that α-syn RT-QuIC detects α-syn aggregates in CSF of patients with DLB, with high diagnostic accuracy. 12–17 …”
Section: Discussionmentioning
confidence: 99%
“…Thelast couple of years have witnessed arenewed interest for the detection of aSyn aggregation as apotential biomark-er for Parkinsonsd isease and other synucleinopathies. [24] PMCAa nd RT-quIC assays were initially developed for the detection of the misfolded prion protein (PrP Sc )and are now used for the diagnostic of transmissible spongiform encepha- (left) and after (right) amplification. 2 mLofC SF were diluted 10 times in 20 mM aSyn K23Q monomer and 10 mMThT.Amplification was carried out at 55 8 8C, without shaking, for 5hours.…”
Section: Forschungsartikel Discussionmentioning
confidence: 99%
“…Detection of abnormal aggregated α-syn in CSF of DLB patients by the RT-QuIC assay was first reported by Fairfoul et al (2016); this was followed by multiple clinical studies. At present, diagnostic methods using skin (Orru et al, 2017) or OM (Orru et al, 2014;Bongianni et al, 2017), which includes CSF, have been reported (Satoh et al, 2017;Ascari et al, 2020;Candelise et al, 2020).…”
Section: α-Synuclein and Real-time Quaking-induced Conversionmentioning
confidence: 99%